Empirical research on corporate credit-ratings: A literature review - Alexander B. Matthies (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
We report on the current state and important older findings of empirical studies on corporate credit ratings and their relationship to ratings of other entities. Specifically, we consider the results of three lines of research: The correlation of credit ratings and corporate default, the influence of ratings on capital markets, and the determinants of credit ratings and rating changes. Results from each individual line are important and relevant for the construction and interpretation of studies in the other two fields, e.g. the choice of statistical methods. Moreover, design and construct of credit ratings and the credit rating scale are essential to understand empirical findings.
Keywords: G20; G30; G32; G24; G34; 330; rating agency; credit ratings; through-the-cycle rating methodology; corporate governance